Study of the actuation behaviour of magnet-polymer morphing composites - Lee, Wilson Kah How (2014)
Magnetic-polymer matrix composites (MagPol) have recently gained interest in the field of actuators due to some of its properties which include exhibiting high strain levels, different actuation modes and the ability to respond reversibly to a magnetic field in an effective manner.